Safeguarding Traditional Cultural Expressions: Legal Regulations for Intellectual Communal Wealth: Melindungi Ekspresi Budaya Tradisional: Peraturan Hukum untuk Kekayaan Komunal Intelektual - Syahnakri, Muhamad; Kurniawan, I Gede Agus (Universitas Muhammadiyah Sidoarjo, 2023)
This study examines the potential reformation of features representing traditional cultural expressions as communal intellectual wealth and the regulatory role of law in safeguarding and promoting this positive orientation. Employing normative legal methodology, existing legal frameworks are analyzed. The research reveals that the reformulation of features embodying traditional cultural expressions is pivotal in preserving their cultural continuity as shared intellectual assets. This process entails safeguarding cultural heritage through intellectual property rights, crafting guidelines, cultural education promotion, empowering local communities, preventing intellectual property abuse, international cooperation, and nurturing local creative industries. Legal regulations play a crucial role in protecting and advancing this positive reformation, encompassing Intellectual Property Rights (IPR) protection, registration and identification of traditional cultural elements, cultural policy formulation, community participation rights and consultation, law enforcement, international collaboration, and public education and awareness. These facets collaboratively ensure that traditional cultural heritage is respected, safeguarded, and judiciously utilized, allowing it to persist, evolve, and contribute positively to national identity and global intellectual wealth. Highlight: Preservation of Cultural Continuity: The study emphasizes the pivotal role of reformulating traditional cultural expressions in maintaining their cultural heritage's continuity as a shared intellectual asset. Multi-Faceted Regulatory Approach: The research underscores the comprehensive legal measures, including Intellectual Property Rights (IPR) protection, cultural policy formulation, and community participation rights, aimed at safeguarding and promoting positive reformation. Global Impact: By ensuring the respectful and judicious utilization of traditional cultural heritage, the study highlights its contribution not only to national identity but also to the broader realm of global intellectual wealth. Keyword: Cultural Heritage Protection, Communal Intellectual Wealth, Legal Regulations, Traditional Cultural Expressions, Intellectual Property Rights.